Application Of Utmost Good Faith Principles In Resolving Insurance Claim Disputes In Indonesian Courts - Musjab, Imam (Journal of Law, Politic and Humanities, 2024)
The purpose of this study is to examine the Application of the Principle of Utmost Good Faith in the Settlement of Insurance Claim Disputes in Indonesian Courts. This study uses a normative juridical legal research method with a case approach to Decision Number 62/Pdt.G/2020/PN.Bpp and is analyzed using an evaluative method. The results of the study show that in the evidentiary process in court proceedings, each party must be able to prove that they have acted in utmost good faith. The insured must be able to show that they have provided complete and accurate information when applying for insurance policies, while the insurer must be able to prove that they have processed claims in utmost good faith and in accordance with the provisions in the policy. If there is any ambiguity in the contract, the court will interpret it in the manner most favorable to the insured (contra proferentem rule), provided that the interpretation is still within the corridor of applicable laws and regulations.